Pemberdayaan Komunitas Peduli Lingkungan melalui Strategi Komunikasi Digital untuk Pelestarian Sungai Perkotaan - Afina Ruqayyah; Rico Fernando Siregar; Wina Puspita Sari; Javier Rafi Putra Sidharto; Arrumaisha Ghaida Puspitasari (Jurnal Bersama Pengabdian Kepada Masyarakat (SAMAMAS), 2026)
Urban river conservation demands not only technical intervention but also strengthened community communication capacity. This community service program aimed to empower the MAT PECI community (Masyarakat Peduli Ciliwung dan Lingkungan Hidup) through digital communication capacity building in support of Ciliwung River conservation in Jakarta. Prior to the program, the community’s Instagram had only 486 followers with 2–3 posts per month and low public engagement, indicating a significant communication capacity gap. Using Participatory Action Research (PAR), activities included digital communication training, social media content mentoring, photography and videography workshops, environmental storytelling, and digital publication strategy development. Pre-test and post-test evaluations showed a significant improvement in participants’ average scores from 51.7 to 85.2 across all dimensions. The program also facilitated formation of an internal media team, a monthly content calendar, and a consistent visual identity, increasing publication frequency to 7–9 posts per month. These findings confirm that community-based digital communication capacity building effectively sustains grassroots environmental conservation movements, aligned with SDGs 6, 11, and 13.